A qualitative analysis on implementing the sewer system for an indigenous village in the influence area of Belo Monte Hydroelectric Plant (Brazil). (28th December 2021) - Cirino, Tarciana Lima; Almeida, Marys Lene Braga; Oliveira, Mariangela Dutra de; Libânio, Marcelo
Abstract: In this article, the project and implementation of the sewer system in the Paquiçamba Village, as a condition for environmental licensing, was investigated. This village is surrounded by the influence of the Belo Monte Hydroelectric Plant (Brazil). This research aimed to characterize the context of ethnodevelopment, thus recognizing the social participation of the indigenous people. The research within a qualitative approach between 2009 and 2018 was based on primary data sources (through structured interviews) and secondary data (electronic files related to the environmental licensing). Data were analysed according to descriptive, focused and selective observations until reaching theoretical saturation. The organization of the data was followed by the organization of the themes, which formed a spiral of interconnected activities based on Creswell's proposal. It was detected that indigenous involvement occurred at some moments in the elaboration of the sewage system project. The maintenance of ancestral habits in the disposal of excreta by a portion of the indigenous people, even with the sewage system in place, makes it essential to broaden the debate on the projects proposed on the environmental licensing processes. The Indigenous can not only have a consultative role, but assume a deliberative participation, being protagonists in conducting their own development. HIGHLIGHTS: The implementation of the sewage system in an indigenous village was investigated as a condition for environmental licensing. The Indigenous continue to transform some habits to resist the negative impacts arising from the construction of the large engineering project. The maintenance of ancestral habits by a portion of the indigenous people makes it essential to broaden the debate on environmental licensing processes.